Profesionalisme Kerja dalam Al-Qur’an - Sobirin Bagus; Tutik Hamidah (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
This study aims to understand the terminology of science and work professionally in the community. Can know the urgency of knowledge in supporting work professionalism and its implementation in society according to the Koran, so that discussions about work professionalism do not always refer to the traditions of China, Singapore, Japan, and countries in the European continent. The method used in this paper is a qualitative method with the type of library research, then describes the terminology of science and work professionalism. Then we will analyze the interpretation of Surat al-Isra '36 from multiple interpretations. Results are ways that we can apply in all the work we do every day so that we can become professionals at work is to place ourselves according to our abilities and expertise at work based on academic qualifications or experience we have, obeying all values and religious norms, recognizing discriminatory attitudes or injustice at work, and avoiding all attitudes and actions that would bridge us to acts of corruption, collusion and nepotism